Experimental Study on the Sliding of WJ-8 Small Resistance Fastener Composite Pad - Zhiping Zeng; Di Wang; Fushan Liu; Abdulmumin A. Shuaibu; Zhihua Lin (Advances in Civil Engineering)
Under long-term temperature loading, long bridges stretch and deform, causing the beam and rail to move relative to each other. This phenomenon could cause a gradual slide of the rail relative to the fastener composite pad and ultimately results in the slipping out of the fastener pad at the end of the ballastless track bridge changes. The slipping out of the fastener composite pad changes the longitudinal resistance of the fastener and causes shock of the train on the rail structure due to direct contact between the rail and the tie, thus inhibiting the normal use of the line. In this paper, a reciprocating tensile test was carried out on a WJ-8 small resistance fastener to explore the breaking process of the fastener composite pad, identify the interaction mechanism of the fastener composite pad under the rail, and ultimately determine the influence of the pad on the longitudinal resistance of the fastener. The results show that the two factors that affect the longitudinal resistance of the fastener under reciprocating loading are the surface roughness and displacement of the fastener composite pad. While the surface roughness of the fastener composite pad is the main influencing factor in the early stage, the displacement of the composite pad has a greater impact on the later stage. The research results of this paper can provide an important reference for the maintenance and repair of ballastless track fasteners on bridges.